The Effect of Regional Original Revenue (Pad) and Transfer Funds on the Financial Efficiency of Local Governments in Indonesia - Putri, Arla Amalia Putri; Masdar, Rahma; Furqan, Andi Chairil; Lucyani, Meldawati; Betty, Betty (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study analyzes the impact of Regional Original Revenue (PAD) and Transfer Funds on the financial efficiency of local governments in Indonesia. This study uses panel data from 548 Provinces/cities/regencies pear year during the 2019-2023 period. The data used was 542 per year of observations or 99.85%, so that the final total of data used in this study was 2,710 observations, showing that PAD has a significant positive effect on the efficiency of regional financial management, which reflects fiscal independence. on the other hand, excessive dependence on transfer fund from the central government has a negative effect on financial efficiency. The study emphasizes the importance of optimizing PAD to improve fiscal independence and efficiency, while reducing dependence on fund transfers from the central government. Data collection in determining samples in this study uses purposive sampling. These findings are important for policy recommendations aimed at strengthening regional fiscal management and sustainable development. further research should explore the broader regional context and additional factors that affect regional financial efficiency.